Transcriptional variations in the wider peritumoral tissue environment of pancreatic cancer. Issue 5 (17th October 2017) - Bauer, Andrea S.; Nazarov, Petr V.; Giese, Nathalia A.; Beghelli, Stefania; Heller, Anette; Greenhalf, William; Costello, Eithne; Muller, Arnaud; Bier, Melanie; Strobel, Oliver; Hackert, Thilo; Vallar, Laurent; et al.
Abstract : Transcriptional profiling was performed on 452 RNA preparations isolated from various types of pancreatic tissue from tumour patients and healthy donors, with a particular focus on peritumoral samples. Pancreatic ductal adenocarcinomas (PDAC) and cystic tumours were most different in these non‐tumorous tissues surrounding them, whereas the actual tumours exhibited rather similar transcript patterns. The environment of cystic tumours was transcriptionally nearly identical to normal pancreas tissue. In contrast, the tissue around PDAC behaved a lot like the tumour, indicating some kind of field defect, while showing far less molecular resemblance to both chronic pancreatitis and healthy tissue. This suggests that the major pathogenic difference between cystic and ductal tumours may be due to their cellular environment rather than the few variations between the tumours. Lack of correlation between DNA methylation and transcript levels makes it unlikely that the observed field defect in the peritumoral tissue of PDAC is controlled to a large extent by such epigenetic regulation. Functionally, a strikingly large number of autophagy‐related transcripts was changed in both PDAC and its peritumoral tissue, but not in other pancreatic tumours. A transcription signature of 15 autophagy‐related genes was established that permits a prognosis of survival with high accuracy and indicates the role of autophagy in tumour biology. Abstract : What's new? To date, relatively few RNA expression data are available on pancreatic tumour types other than pancreatic ductal adenocarcinoma (PDAC) or peritumoral tissues. Here, the authors found that transcriptionally, peritumoral tissues of PDAC behave much like the tumours, although resembling normal tissue in cell composition. In contrast, transcription in the environment of cystic pancreatic tumours is basically identical to that of normal tissue, suggesting an effect of peritumoral tissues on the strong pathogenic difference between PDAC and cystic tumours. At the functional level, autophagy‐related genes are uniquely changed in PDAC and its peritumoral tissue, with their expression variation predicting patient survival.